Recursos digitales en el portal web del Ministerio de Educación que son utilizados en el proceso de enseñanza-aprendizaje de la asignatura de Lengua y Literatura en la Escuela de Educación Básica Particular Carpe Diem durante el año lectivo 2023-2024. - Salinas Pintado, Carmen Maribel (2024)
The present Curricular Integration Work entitled "Digital Resources on the Ministry of Education's Website Used in the Teaching-Learning Process of Language and Literature Subject at Carpe Diem Private Basic Education School during the Academic Year 2023-2024" aims to analyze the digital resources available on the Ministry of Education's website utilized by teachers in the teaching-learning process of the Language and Literature subject at Carpe Diem Private Basic Education School during the academic year 2023-2024. The methodological approach of the research is based on a transversal method, with a quantitative and exploratory/descriptive focus. It is noteworthy that a questionnaire using the survey technique was applied, with a sample consisting of 12 Language and Literature subject teachers. Based on the results obtained, it was found that the most utilized digital resource from the Ecuadorian Ministry is "El gato atrapado" with a total percentage of 36%, while "Literatura dibujada Aprender a tiempo" and "Juntos leemos" were the two resources that were never used, both with a total percentage of 16%. Finally, it is concluded that the appropriate use of digital educational resources in the classroom positively enhances the teaching-learning process of Language and Literature. Key words: Language and Literature, Ministry of Education's website, Teaching-Learning Process, Digital Resources.